Dydaktyka zorientowana na współpracę równych. Typy relacji ze studentami podczas wspólnej pracy badawczej - Kowzan, Piotr (Hybris, 2017)
Communities of peers in search of truth do not emerge in higher education institutions any more, which is one of the reason for universities' growing weakness. The aim of the paper is to help academic teachers organize research together with students during regular classes. This includes assessing academic productivity of meetings regarding typical relations between teachers and students: feudal, reciprocal and baseline communist. It starts with the analysis of possibilities and necessities of academic teaching, which is based on connections between the before-mentioned relations and forms of working together in a group, which must be adequate to the number of participants. Next, an analysis of cases when the challenges students are posed with are not balanced with the skills they have gained, leads to studying consequences of students' frustration and ways they can take initiative and responsibility for changing the type of relation between teachers and themselves. As a result, we have a model in which personal relations, forms of co-working and the scale of involvement needed for a research project are the core issues that must be taken into account in order to transform classes into the time of collective research.